Ghrelin and Breast Cancer: Emerging Roles in Obesity, Estrogen Regulation, and Cancer - Au, CheukMan Cherie; Furness, John B.; Brown, Kristy A. (Frontiers in Oncology, 2017)
Local and systemic factors have been shown to drive the growth of breast cancer cells in postmenopausal obese women, who have increased risk of estrogen receptor-positive breast cancer. Estrogens, produced locally in the breast fat by the enzyme aromatase, have an important role in promoting cancer cell proliferation. Ghrelin, a 28-amino acid peptide hormone, may also influence cancer growth. This peptide is produced in the stomach and acts centrally to regulate appetite and growth hormone release. Circulating levels of ghrelin, and its unacylated form, des-acyl ghrelin, are almost always inversely correlated with obesity, and these peptide hormones have recently been shown to inhibit adipose tissue aromatase expression. Ghrelin and des-acyl ghrelin have also been shown to be produced by some tumor cells and influence tumor growth. The ghrelin/des-acyl ghrelin–cancer axis is complex, one reason being that tumor cells have been shown to express splice variants of ghrelin, and ghrelin and des-acyl ghrelin might act at receptors other than the cognate ghrelin receptor, growth hormone secretagogue receptor 1a, in tumors. Effects of ghrelin and des-acyl ghrelin on energy homeostasis may also affect tumor development and growth. This review will summarize our current understanding of the role of ghrelin and des-acyl ghrelin in hormone-dependent cancers, breast cancer in particular.